Pengaruh model pembelajaran discovery learning berbantuan media replika simulasi bencana terhadap hasil belajar siswa SD - Nur Aini Rikhayana; Fina Fakhriyah; Yuni Ratnasari (COLLASE (Creative of Learning Students Elementary Education), 2026)
The learning process carried out monotonously can cause low student learning outcomes. This is evidenced by the conditions at SD Negeri Tambahmulyo 01 where the average student learning outcomes obtained were 73% which is classified as low in the subject of science. The discovery learning model assisted by simulation replica learning media in learning that requires students to be active in learning by finding and investigating solutions to a problem so that results will be obtained that last a long time in memory. This study was conducted to test the hypothesis (1) There is a difference in the average student learning outcomes before and after the use of the Discovery Learning learning model assisted by disaster simulation replica learning media, (2) there is an increase in learning outcomes obtained by students with the use of the Discovery Learning learning model assisted by disaster simulation replica learning media. This study was conducted at SD Negeri Tambahmulyo 01 with a sample of 23 fifth grade students. This study used a quantitative Pre-Experimental research method with a One Group Pretest-Posttest research design. The data collection techniques used were observation, interviews, tests, and documentation. The data analysis techniques used were normality test, Paired Sample T-test, and N-Gain test. Keywords: Discovery Learning, Learning Outcomes, Disaster Simulation Replica Media